(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction : Chitosan from milkfish scale chitin is a polymer material that is biocompatible, biodegradable, and non-toxic. Chitosan has been used as an antimicrobial, anti-inflammatory, bioactivity with dental materials, hemostasis, wound healing, and bone repair. Wound healing after tooth extraction is a pathophysiological process involves proliferation, cell migration, and tissue remodeling. The ability of chitosan to regenerate tissue is use as a soft tissue regeneration material and scaffold for bone regeneration. This literature review aims to discuss the ability of chitosan contained in milkfish scales to regenerate bone tissue and soft tissue after tooth extraction. Methods: Data were collected through article searches on PubMed and Cochrane published from 2016 to 2022. Data search was conducted using keywords; ((Tooth Extraction) OR (Bone Regeneration)) OR (Soft Tissue Healing)) AND (Chitosan). Result: An initial search of Pubmed and Cochrane found 392 articles. Furthermore, 357 articles were excluded because they did not meet the inclusion criteria desired by the author in the title and abstract, or there were duplications, so that 35 articles were obtained. Then from these 35 articles, 23 articles were excluded, and the final results were 12 articles that would be reviewed and included in the synthesis table. Conclusion: Milkfish scale chitosan has the potential as an anti-inflammatory agent, stimulates the activity of fibroblasts, osteoblasts, and mesenchymal stem cell differentiation, and osteoconductive bone regeneration scaffold. However, the utilization will be better when combined with polymers/biomaterials, and/or other bioactive molecules to improve mechanical properties, protein absorption, and biomineralization of chitosan.